2012
DOI: 10.3109/01443615.2012.656743
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of obstetric professionals to inform parents regarding potential outcome of premature infants

Abstract: Parents often regard obstetric professionals as an important source of information regarding prematurity. However, there is no information regarding the readiness of these obstetric professionals to inform expectant parents of the potential outcomes of premature infants. Using a self-report questionnaire, we determined the knowledge of obstetric professionals regarding outcomes of premature infants, and gauged their confidence in providing this information to expectant parents. Some 50% of obstetric profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The most common risk factors for preterm birth included prior spontaneous preterm birth and multifetal gestation. The median GA at enrollment was 20 (range, [18][19][20][21][22] weeks. Twenty participants were part of a mother/father pair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common risk factors for preterm birth included prior spontaneous preterm birth and multifetal gestation. The median GA at enrollment was 20 (range, [18][19][20][21][22] weeks. Twenty participants were part of a mother/father pair.…”
Section: Resultsmentioning
confidence: 99%
“…First, obstetric healthcare providers are hesitant to provide premature infant health outcome information to parents, especially regarding neurodevelopmental outcomes. 20,21 Secondly, obstetric healthcare providers are reluctant to risk frightening pregnant women with discussions of potential neonatal death and disability, since most pregnancies will not result in a preterm birth. 22 Finally, there is concern that the parents will not be receptive to anticipatory education unless the threat of preterm birth is a "clear and present danger."…”
Section: Introductionmentioning
confidence: 99%
“…Einaudi et al (2013) examined physicians' knowledge in the management of children born extremely preterm, finding a need for information on methods of assessment to inform care. Powell et al (2012) reported that 50% of obstetric professionals found answering parental questions regarding their preterm infants challenging. Parker et al (2012) identified that doctors were unaware of the stress levels felt by parents of preterm babies after discharge and were subsequently unprepared to support them through discharge.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Powell et al. (2012) reported that 50% of obstetric professionals found answering parental questions regarding their preterm infants challenging. Parker et al.…”
Section: Introductionmentioning
confidence: 99%